2012
DOI: 10.1115/1.4006296
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient 3D Model of Heterogeneous Materials for Elastic Contact Applications Using Multigrid Methods

Abstract: International audienceAbstract: A 3D graded coating/substrate model based on multigrid techniques within a finite difference frame work is presented. Localized refinement is implemented to optimize memory requirement and computing time. Validation of the solver is performed through a comparison with analytical results for (i) a homogeneous material and (ii) a graded material. The algorithm performance is analyzed through a parametric study describing the influence of layer thickness (0.01 < t/a < 10) and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…(12) from [40], the maximum difference is 1.3% for E c =E s ¼ 0:05, which shows the curve fit formula to be quite accurate. Boffy et al [27] used a multigrid method to solve the elastic problem combined with a conjugate gradient algorithm to determine the contact pressure for the same problem. The present results are also in very good agreement with those findings, as should obviously be the case.…”
Section: Coated Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…(12) from [40], the maximum difference is 1.3% for E c =E s ¼ 0:05, which shows the curve fit formula to be quite accurate. Boffy et al [27] used a multigrid method to solve the elastic problem combined with a conjugate gradient algorithm to determine the contact pressure for the same problem. The present results are also in very good agreement with those findings, as should obviously be the case.…”
Section: Coated Materialsmentioning
confidence: 99%
“…the equations and unknowns are defined at each point of the grid, see [27,35]. Higher order discretizations can be developed using, e.g., the so-called compact schemes, see [42].…”
Section: Appendix a Discrete Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [12,13], Boffy et al applied multigrid method to the 3D stress filed solution in heterogeneous and strong heterogeneous material with given contact pressure distribution. It is proved the developed multigrid algorithm possess high accuracy and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Boffy et al. performed a contact analysis of deformable bodies loaded normally and tangentially against graded layers bonded to heterogeneous substrates. Recently, Barber and Ciavarella proposed an approximate JKR solution for the adhesive contact of anisotropic materials, and found that the dimensionless degree of anisotropy can significantly increase the pull‐off force.…”
Section: Introductionmentioning
confidence: 99%